Unbound granular base course with shallow foundation concept - Siripun, K.; Jitsangiam, Peerapong; Nikraz, H. (2011)
This study aims to introduce alternative design procedures for a flexible pavement base course by utilizing the ultimate strength criteria with sophisticated laboratory results of base course materials. Current pavement design mostly avoids all complicated behaviours of an unbound granular base layer considered only as a layer transferring traffic loads to underneath layers regardless of the base course deterioration. Based on the design protocol, there are only the design criterion of the horizontal tension and the vertical compression occurring at the bottom of asphalt layer and at the top of subgrade, respectively. The real behaviour of a base course under traffic loads has been rarely accounted for in pavement design protocol. Nowadays, traffic is growing in terms of magnitudes and quantities and causing premature deterioration in a base course layer leading to major damage in pavements. The study presents theoretically the more suitable approach of the stress and strain distribution in a flexible pavement using the finite element method. An example of a conventional pavement structure consisting of a surfacing, a base course, a sub base course and a subgrade with a single wheel load of 750 kPa standard pressure was selected was established to investigate all pavement phenomena. The effects of uniform design pressure and material attributes which were generated by traffic were investigated. Moreover, the new design criteria for an unbound granular layer were defined as the ultimate strength design and the bearing capacity factor resulting from the application of the shallow foundation bearing capacity concept within the California Bearing Ratio (CBR) results. Our findings were reported and used to draw up the guideline and recommendation on the current pavement analysis and design.